Inputs in distress: Geoeconomic fragmentation and firms' sourcing - Ludovic Panon; Laura Lebastard; Michele Mancini; Alessandro Borin; Peonare Caka; Gianmarco Cariola; Dennis Essers; Elena Gentili; Andrea Linarello; Tullia Padellini; Francisco Requena Silvente; Jacopo Timini (European Central Bank (ECB), 2024)
We study how disruptions to the supply of foreign critical inputs (FCIs) - that is, inputs primarily sourced from extra-EU countries with highly concentrated supply, advanced technology products, or which are key to the green transition - might affect value added at different levels of aggregation. Using firm-level customs and balance sheet data for Belgium, France, Italy, Slovenia and Spain, our framework allows us to assess how much geoeconomic fragmentation might affect European economies differently. Our baseline calibration suggests that a 50% reduction in imports of FCIs from China and other countries with similar geopolitical orientations would result in sizable losses of value added with significant heterogeneity across firms, sectors, regions and countries, driven by the heterogeneous exposure of firms. Our findings show that the short-term costs of supply disruptions of FCIs can be substantial, especially if firms cannot easily switch away from these inputs.
Keywords: F10; F14; F50; F60; 330; Geoeconomic fragmentation; global value chains; global sourcing; international trade; imported inputs